FORMATION OF THE CULTURE OF FUTURE TEACHERS IN CONTEXTS OF PERSONALITY-ORIENTED EDUCATION (Pedagogy of Higher and Secondary Education, 2003)
In this article it is spoken about necessity o f formation o f internal culture of the future teachers. It is offered to consider development o f education in a context o f culture.